Development of a performance diagnosis of the anaerobic strength endurance of the forearm flexor muscles in sport climbing - Schöffl, V. R.; Möckel, F.; Köstermeyer, G.; Roloff, I.; Küpper, T. (International Journal of Sports Medicine, 2006)
The anaerobic strength endurance of the forearm flexor muscles represents the main limiting factor in modern sports climbing. Only isometric testing has been performed so far in order to evaluate this factor. Since climbing involves intermittent isometric contraction as well as dynamic movements, a pure isometric testing is too unspecific. The present paper demonstrates a specific performance diagnosis using a rotating climbing wall as a climbing ergometer. Twenty-eight male climbers performed a step test. According to their climbing level they were divided into three groups with different inclinations of the wall. Maximum blood lactate was 5.0 ± 1.3 mmol/l (mean ± sd), climbing length 39.1 ± 15.7 m, and heart rate 185 ± 10.7 bpm. The mean number of steps performed was 5.8 ± 2.5 and the mean slope of the blood lactate graph (regression equitation) was 0.57 ± 0.4. The specific climbing recovering ability is documented with the so called heart rate difference and additionally the positive effects of a non specific, aerobic, basic endurance training are demonstrated. A mathematical analysis of the most important performance limiting test results enabled us to determine a strength-endurance factor that can be applied for cross- and longitudinal-section comparisons.